2018
DOI: 10.1073/pnas.1810755115
|View full text |Cite
|
Sign up to set email alerts
|

Remote subsurface ocean temperature as a predictor of Atlantic hurricane activity

Abstract: Predicting North Atlantic hurricane activity months in advance is of great potential societal significance. The ocean temperature, both in terms of North Atlantic/tropical averages and upper ocean heat content, is demonstrated to be a significant predictor. To investigate the relationship between the thermal state of the Atlantic Ocean and the tropical cyclone (TC) activity in terms of accumulated cyclone energy (ACE), we use observed 1980–2015 TC records and a 1/4° resolution global ocean reanalysis. This pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…The frequency (count per year) is the simplest metric of TC activity but is strongly sensitive to the tracking algorithm, model resolution, observing system changes, and other aspects (Roberts et al, 2020). The ACE index (Bell et al, 2000) is an integrated measure of TC activity, and its variability is more robust (Scoccimarro et al, 2018; Villarini & Vecchi, 2013; Zarzycki & Ullrich, 2017). We use the same method as Camp et al (2015) and calculate ACE throughout the lifetime of each model storm during its warm core phase using winds at 925 hPa.…”
Section: Methodsmentioning
confidence: 99%
“…The frequency (count per year) is the simplest metric of TC activity but is strongly sensitive to the tracking algorithm, model resolution, observing system changes, and other aspects (Roberts et al, 2020). The ACE index (Bell et al, 2000) is an integrated measure of TC activity, and its variability is more robust (Scoccimarro et al, 2018; Villarini & Vecchi, 2013; Zarzycki & Ullrich, 2017). We use the same method as Camp et al (2015) and calculate ACE throughout the lifetime of each model storm during its warm core phase using winds at 925 hPa.…”
Section: Methodsmentioning
confidence: 99%
“…The frequency (count per year) is the simplest metric of TC activity but is strongly sensitive to the tracking algorithm, model resolution, observing system changes, and other aspects (Roberts et al, 2020). The ACE index (Bell et al, 2000) is an integrated measure of TC activity, and its variability is more robust (Scoccimarro et al, 2018;Villarini & Vecchi, 2013;. We use the same method as Camp et al (2015) and calculate ACE throughout the lifetime of each model storm during its warm core phase using winds at 925 hPa.…”
Section: Metricsmentioning
confidence: 99%
“…On the short time scale, an important role is played by observational systems such as radiosondes, coastal weather radars and reconnaissance flights, also due to their contribution in providing the detailed initial environmental state description necessary for modeling TC development. A recent work (Scoccimarro et al, 2018) demonstrated the importance of the subsurface temperature in modulating TC activity on seasonal time scales, specifically its fundamental role of monitoring of the eastern Atlantic sector (in red in Figure 4). Moving from short to seasonal and even longer time scales, an important role is played by the ocean since the main source of energy for TC development resides in this "compartment" of the climate system.…”
Section: Tropical Cyclonesmentioning
confidence: 99%